Vascular parkinsonism--an update - Rektor, Ivan; Rektorová, Irena; Kubová, Dagmar (Journal of the neurological sciences, 2006)
Vascular parkinsonism (VP) is a heterogeneous clinical entity. The idea of a relationship between cerebral vascular disease and parkinsonism may be traced back to the 1920s, when the diagnostic unit called "arteriosclerotic parkinsonism", a predecessor of VP, was established. This review is concerned with historical and contemporary views regarding the possible vascular genesis of parkinsonism. Confusion persists as a result of vaguely defined diagnostic criteria. The following types of simultaneous occurrence of parkinsonism and cerebral vascular disease (CVD) may be recognised: 1. gait disorders of the lower body parkinsonism type are caused mostly by white matter lesions in the frontal lobes; such disorders may require a diagnosis of vascular origin. We suggest replacing the term "lower body parkinsonism" with a more appropriate term not including the word "parkinsonism": an alternative term could be "cerebrovascular gait disorder"; 2. if the signs and symptoms are typical for idiopathic Parkinson's disease (IPD), the coincidence of IPD and CVD should be considered; 3. if the symptoms of parkinsonism are neither typical for IPD nor for VP, and there are clinical or MR signs of CVD, VP should be regarded as possible when alternative causes are excluded; 4. if the symptoms of parkinsonism and clinical and MR signs are typical for VP, VP should be regarded as probable; 5. if a stroke affecting the contralateral basal ganglia is followed by the occurrence of hemiparkinsonism, the diagnosis of VP is unambiguous. Vascular parkinsonism (VP) is probably one of the most frequently erroneous neurological diagnoses. The reason for this misdiagnosis is that both cerebral vascular disease (CVD) and parkinsonism usually occur at the same age. Due to the high incidence of CVD, it is possible for CVD and idiopathic Parkinson's disease (IPD) to coincide in some cases. Another reason for the misdiagnosis is that the concept of VP lacks clarity. This review aims to contribute to an improved understanding of VP in clinical practice. In this context, the term "CVD" is understood in the broad sense of a brain impairment caused by cerebral vessel pathology. It covers various concepts, as some authors use the term CVD to mean a manifestation of vascular lesions in pathologico-anatomical material or in the imaging techniques; others mean the history and clinical manifestation of cerebral ischaemia, or, more rarely, haemorrhage. The term CVD may cover large vessel disease as well as small vessel disease. This means that territorial and lacunar infarcts and white matter lesions (WML) are all considered as CVD.
Keywords: magnetická rezonanční tomografie; Cerebrovascular Disorders; Magnetic Resonance Imaging; Humans; cerebrovaskulární poruchy; History, 20th Century; dějiny 20. století; lidé; Parkinsonian Disorders; parkinsonské poruchy